2004
DOI: 10.1111/j.1440-1681.2004.04059.x
|View full text |Cite
|
Sign up to set email alerts
|

T393C polymorphism of GNAS1 associated with the autonomic nervous system in young, healthy Japanese subjects

Abstract: 1. T393C polymorphism of the gene encoding the Gs-protein alpha-subunit (GNAS1) has been reported recently to be associated with hypertension in which dysfunctions of the autonomic nervous system (ANS) are closely involved. In the present study, the association of this polymorphism with ANS activity was investigated in young, healthy Japanese males. 2. Four hundred and one subjects were genotyped for the T393C polymorphism of GNAS1 by polymerase chain reaction-restriction fragment length polymorphism. Autonomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…In a small study, GNAS rs7121 alleles were associated with blood pressure-lowering effects of the ␤-blocker timolol applied as an ophthalmic preparation (Nieminen et al, 2005). There is also evidence that GNAS rs7121 alleles affect the activity of the autonomic nervous system Yasuda et al, 2004). G␣ S is expressed ubiquitously, and recent reports suggest that the rs7121 variant is also a predictor for cancer survival (Frey et al, 2005(Frey et al, , 2006 and psychiatric traits (Zill et al, 2002;Minoretti et al, 2006).…”
Section: ␤-Antagonistmentioning
confidence: 99%
“…In a small study, GNAS rs7121 alleles were associated with blood pressure-lowering effects of the ␤-blocker timolol applied as an ophthalmic preparation (Nieminen et al, 2005). There is also evidence that GNAS rs7121 alleles affect the activity of the autonomic nervous system Yasuda et al, 2004). G␣ S is expressed ubiquitously, and recent reports suggest that the rs7121 variant is also a predictor for cancer survival (Frey et al, 2005(Frey et al, , 2006 and psychiatric traits (Zill et al, 2002;Minoretti et al, 2006).…”
Section: ␤-Antagonistmentioning
confidence: 99%
“…Since this first description, the GNAS1 T393C polymorphism could be associated with many other phenotypes. [19][20][21][22][23][24][25] Although these multiple associations of this polymorphism with different Gas-mediated cascades indicate a true effect of T393C, the molecular mechanism remains obscure. Definitely, it has been shown in different tissues, that Gas mRNA expression is increased in TT genotypes.…”
mentioning
confidence: 99%
“…For example, Souza [5] found cardiac sympathetic overactivity of the heart rate control and decreased low frequency band (LFB,0.20-0.60Hz) of heart rate power in the L-NAME hypertensive rat and Chowdhary [6] found that NO increased high-frequency (HF) component of heart rate variability. It has been reported that genetic variability can influence heart rate variability in human, such as the GNAS1 T393C polymorphisms associated with ANS activity in young healthy Japanese subjects [7] . Wang [8] reported that approximately 30% of the variance of nitric oxide level in the human body is due to nitric oxide synthase gene polymorphisms, it suggests variability of nitric oxide and nitric oxide synthase in the pathogenesis of some diseases may be due to nitric oxide synthase polymorphisms.…”
Section: Introductionmentioning
confidence: 99%